Determinants and impact of calcium oxalate crystal deposition on renal outcomes in acute kidney injury patients - Weiwei Yang; Tao Zhao; Xuejing Chen; Suxia Wang; Yu Wang; Tao Su (Renal Failure)
Objectives Calcium oxalate (CaOx) crystal deposition in acute kidney injury (AKI) patients is under recognized but impacts renal outcomes. This study investigates its determinants and effects.Methods We studied 814 AKI patients with native kidney biopsies from 2011 to 2020, identifying CaOx crystal deposition severity (mild: <5, moderate: 5–10, severe: >10 crystals per section). We assessed factors like urinary oxalate, citrate, urate, electrolytes, pH, tubular calcification index, and SLC26A6 expression, comparing them with creatinine-matched AKI controls without oxalosis. We analyzed how these factors relate to CaOx severity and their impact on renal recovery (eGFR < 15 mL/min/1.73 m2 at 3-month follow-up).Results CaOx crystal deposition was found in 3.9% of the AKI cohort (32 cases), with 72% due to nephrotoxic medication-induced tubulointerstitial nephritis. Diuretic use, higher urinary oxalate-to-citrate ratio induced by hypocitraturia, and tubular calcification index were significant contributors to moderate and/or severe CaOx deposition. Poor baseline renal function, low urinary chloride, high uric acid and urea nitrogen, tubular SLC26A6 overexpression, and glomerular sclerosis were also associated with moderate-to-severe CaOx deposition. Kidney recovery was delayed, with 43.8%, 31.2%, and 18.8% of patients having eGFR < 15 mL/min/1.73 m2 at 4, 12, and 24-week post-injury. Poor outcomes were linked to high urinary α1-microglobulin-to-creatinine (α1-MG/C) ratios and active tubular injury scores. Univariate analysis showed a strong link between this ratio and poor renal outcomes, independent of oxalosis severity.Conclusions In AKI, CaOx deposition is common despite declining GFR. Factors worsening tubular injury, not just oxalate-to-citrate ratios, are key to understanding impaired renal recovery.